2012
DOI: 10.6023/cjoc1202092
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Petasis Reaction

et al.

Abstract: Petasis reaction is a powerful method for the synthesis of α-amino acids, β-amino alcohols and their derivatives. Chiral Petasis reaction has been applied in synthesis of nature products and drugs. This review describes the mechanism, reaction components and reaction conditions of Petasis reaction, and the applications of Petasis reaction are also discussed in the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…On the other hand, there has been a growing interest in transition-metal-free functionalization of organoboronates, which offers a powerful tool for the construction of C-C bond as illustrated by the Petasis-Borono Mannich reaction (PBM). Considering that there are already many outstanding comprehensive reviews with respect to PBM and relevant nucleophilic additions of organoborons to unsaturated bonds, [37] those reactions will not be discussed herein. In this section, we wish to focus on recent examples in which C-C bonds are constructed via a 1,2-aryl migration pathway.…”
Section: Carbon-carbon Bond Formationmentioning
confidence: 99%
“…On the other hand, there has been a growing interest in transition-metal-free functionalization of organoboronates, which offers a powerful tool for the construction of C-C bond as illustrated by the Petasis-Borono Mannich reaction (PBM). Considering that there are already many outstanding comprehensive reviews with respect to PBM and relevant nucleophilic additions of organoborons to unsaturated bonds, [37] those reactions will not be discussed herein. In this section, we wish to focus on recent examples in which C-C bonds are constructed via a 1,2-aryl migration pathway.…”
Section: Carbon-carbon Bond Formationmentioning
confidence: 99%
“…The key intermediate to all seven target molecules would be the Petasis borono Mannich reaction product C. [24][25][26][27][28] This reaction delivers five of the seven stereogenic centers of the yield. 26,27 Whilst spectroscopic analysis confirmed the formation of 16, it was found that the HCl salt of 16 was highly crystalline 32 and so X-ray crystallographic studies were then used to confirm the anti-stereochemical outcome of the newly formed 1,2-amino alcohol.…”
Section: Resultsmentioning
confidence: 99%
“…A retrosynthetic analysis shown in Scheme suggests that the diol configuration at C6 and C7 in A can be manipulated at a later stage and will allow access to compounds 6 – 12 . The key intermediate to all seven target molecules would be the Petasis borono Mannich reaction product C . This reaction delivers five of the seven stereogenic centers of the target molecules via the three component reaction of the protected L-xylose 13 and two commercially available precursors, either ( R )- or ( S )-α-methylallyl amine·HCl 14 and trans -2-phenylvinyl boronic acid 15 (Scheme ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The Petasis reaction, referred to also as the boronic acid Mannich reaction, is an extremely useful procedure providing molecules of complex architecture. [13][14][15] It is a three-component reaction between amine, organoborate and aldehyde or ketone and proceeds via an imine with the organic ligand of the boronic acid acting as the nucleophile, like the role of the enolizable ketone component in the original Mannich reaction.…”
Section: Introductionmentioning
confidence: 99%